2000
DOI: 10.1507/endocrj.47.285
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lymphocytic Infundibuloneurohypophysitis Showing Diabetes Insipidus Followed by Anterior Hypopituitarism Associated with Thrombasthenia.

Abstract: Abstract.We report a case of a 42-year old male patient with diabetes insipidus followed by anterior hypopituitarism associated with thrombasthenia.The patient had been diagnosed with thrombasthenia since the age of 19. He was admitted and diagnosed as diabetes insipidus in 1995. Although T1-weighted image of magnetic resonance imaging (MRI) showed empty sella and partial pituitary stalk hypertrophy, the anterior pituitary functions were normal at that time. Three years later, he was re-admitted after an episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Access to the pituitary gland is not easy, nor is antipituitary antibody detection [52][53][54][55]. This would support a diagnosis of present or past hypophysitis.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the pituitary gland is not easy, nor is antipituitary antibody detection [52][53][54][55]. This would support a diagnosis of present or past hypophysitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although lymphocytic hypophysitis can have similar symptoms and radiologic findings, it usually regresses spontaneously. The features of the MRI indicative of lymphocytic hypophysitis include loss of the hyperintense “bright spot” signal of the posterior pituitary on T1-weighted images, enlargement of the posterior gland, or an isodense homogeneous mass [9]. None of these features were noted in our patient, which led us to exclude the possibility of lymphocytic hypophysitis.…”
Section: Discussionmentioning
confidence: 71%
“…We observed that overall clinical response and especially visual field recovery was better with high and very high dose vs medium dose glucocorticoids. A pathophysiological explanation for improved clinical response to very high doses (>100 mg/day) is probably related to the non-specific non-genomic actions, where higher supra-physiological doses (>100 mg/day) have anti-inflammatory effects whereas lower supra-physiological doses (<30 mg/day) are just immunomodulatory (5,19). It has been demonstrated that the non-genomic action of glucocorticoids has a log-linear relationship with dose after ≥30 mg/day, below which it is negligible ( 5).…”
Section: Discussionmentioning
confidence: 99%